Prevalence and Effects of Self-Medication Practice among Pharmacy Students: A Cross-Sectional Study in Karachi: Prevalence and Effects of Self-Medication Practice among Pharmacy Students - Anjum, Leena; Fraz, Tayyab Raza; Islam, Fiza; Iftikhar, Leena; Khalid, Ammara (Pakistan Journal of Health Sciences, 2025)
The prevalence of self-medication is notably high among medical students compared to the general population, which is primarily attributed to advanced knowledge of pharmacology and easier access to pharmaceuticals either through educational resources or hospital attachments, potentially underestimating the risks involved. Objectives: To determine the prevalence and effects of self-medication practice among pharmacy students: a cross-sectional study in Karachi. Methods: The study employed a cross-sectional descriptive design conducted on 283 pharmacy students using a structured, self-administered questionnaire developed specifically. The collected data were analyzed by SPSS-21 software. Results: The outcomes revealed the response rate of 92.93%, with the largest group of participants (23%) being first-year students, comprised mainly female respondents (72.24%), between the ages of 21-23. The relationship between both age and year of study with the usage of self-medication without consulting a doctor is found to be significant. Students were engaged in the use of self-medication occasionally. The commonly reported symptoms and conditions practiced were headaches (55.1%). However, a statistically significant relationship was observed between certain medical conditions, particularly fever, diarrhea, and nausea/vomiting, and gender. Further evaluated perceptions of the safety of self-medication, with statistical analysis highlighting significant associations with both age (p=0.036) and year of study (p=0.014). Conclusions: The Prevalence of self-medication among pharmacy students is high. It is needed to focus on developing and implementing programmes about the risks of self-medication, and to ensure self-practices along with a control system and monitoring of drug sales by health decision-makers and policymakers.